Kampanye Kebijakan di TikTok: Pengaruhnya Terhadap Kesadaran dan Sikap Generasi Z Kota Palangka Raya - Maharani, Shafa Nabilla Dwi Annisa; Lestari, Ayu; Selvia, Fitriana; Syamsuri, Syamsuri; Suprayitno, Suprayitno (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2025)
This study explores how policy advocacy campaigns delivered through TikTok shape the awareness and attitudes of Generation Z in Palangka Raya City. Although the platform has rapidly become a prominent channel for public information, academic research has not sufficiently examined how persuasive policy messages spread among young audiences within an environment driven by personalized digital algorithms. To address this gap, the study adopts the Diffusion of Innovation framework to understand how exposure to policy-oriented content influences the cognitive and attitudinal responses of TikTok users from Generation Z. Using a quantitative approach, the research engaged a group of respondents selected purposively from the local TikTok user population. Data were obtained through an online questionnaire that captured perceptions and behavioral tendencies, and the results were analyzed using a statistical model appropriate for measuring directional influence. The findings indicate that policy advocacy content on TikTok plays a meaningful role in enhancing both awareness and attitudes among young users in the city. These results demonstrate that the Diffusion of Innovation framework remains relevant for understanding message dissemination in contemporary digital media contexts. Moreover, the study shows that TikTok functions not only as an entertainment platform but also as an effective medium for government communication aimed at younger audiences. The research contributes to the field of digital policy communication by emphasizing the significance of platform-specific content dynamics and provides practical insights for policymakers seeking to improve engagement and understanding among Generation Z in an increasingly digital public sphere.